The clinical significance of metastatic breast carcinoma to intramammary lymph node. Issue 2 (6th October 2019) - Khoury, Thaer; Fang, Yisheng; Karabakhtsian, Rouzan; Mokhtar Desouki, Mohamed; Nayak, Anupma; Hanna, Mathew; Sanati, Souzan; Peng, Xuan; Yan, Li; Li, Xiaoxian; Fadare, Oluwole; Ambrosone, Christine; et al.
Abstract: The incidence of involved intramammary lymph node (intra‐MLN) with breast carcinoma (BC) is rare. Its clinical significance and impact on the clinical decision making is unclear. A total of 113 BC cases with at least one positive intra‐MLN were collected from 11 academic institutions. The inclusion criteria were subsequent axillary lymph node dissection, and the availability of information on T‐stage, size of node metastasis, extranodal extension status, biomarkers status, and clinical follow‐up. Stage 4 cases and/or neo‐adjuvant treated patients were excluded. AJCC TN‐stage was calculated twice, with and without intra‐MLN. Five‐year overall survival (OS) and relapse (local and/or distant)‐free survival (RFS) were calculated and correlated with the clinicopathologic variables. Excluding intra‐MLN, TN‐stage correlated with OS ( P  = .016) but not with RFS ( P  = .19). However, when intra‐MLN was included, TN‐stage correlated with both OS ( P  < .001) and RFS ( P  = .016). In the multivariate analysis, when intra‐MLN was excluded, only radiation therapy (RT) correlated with RFS (HR = 0.19, 95% CI: 0.054‐0.66, P  = .009). However, when intra‐MLN was included in the TN‐stage both RT (HR = 0.13, 95% CI: 0.04‐0.45, P  = .001) and TN‐stage 3 (HR = 8.92, 95% CI: 1.47‐54, P  = .017) correlated with RFS. Tumor multifocality was the only variable correlated with OS when the intra‐MLN involvement was excluded. When intra‐MLN was included, multifocality became insignificant but TN‐stage 3 correlated with OS (HR = 8.59, 95% CI: 1.06‐69.71, P  = .044). Positive intra‐MLN is an independent factor in predicting both RFS and OS.